ANALISIS RASIONALITAS PENGGUNAAN OBAT PADA PASIEN HIPERTENSI DI PUSKESMAS BUMIAYU TAHUN 2021 - Umatus Sodiqoh; Aziez Ismunandar; Luthfi Hidayat Maulana (Prodi Farmasi Fakultas Sains dan Teknologi Universitas Peradaban, 2021)
Hypertension is an unrelated inherent disease that became one of the main causes of premature death in the world (Hariawan & Tatisina, 2020). Hypertension in Bumiayu Health Center is the most suspected disease in order of number one so that it is necessary to be analyzed the rationality of hypertensi medicine for the achievement of the right and precise hypertension medicine. This research aims to Knowing the pattern of use of antihypertension medicine in Bumiayu Healt Center, knowing the level of rationality of antihypertension medicine use in Bumiayu Health Center, and knowing the outcome of the use of antihypertension medicine in Bumiayu Health Center. Method for this study uses non-experimental observation methods of descriptive analysis with cohort study design through interviewed hypertension patients in Bumiayu Health Center with ethical clearance number B.1524/800.2/iii/2021. The population in this study of 6,514 patients, collect sample is 98 using the Slovin formula and meets the inclusion criteria. The inclusion criteria in this study are hypertension patients recorded in the outpatient register book and get prescription of hypertension drugs, age-based hypertension patients > 45 years, suffering from hypertension with or without complications, and patients are willing to be respondents. The exclusion criteria in this study were respondents refused to participate and responds died. The results of the rationality of medicine use in this study amounted to 53.1% with the patient outcome of 52% of its blood pressure is stable and the result of linear regression shows that there is an effect of rationality of medicine use providing hypertension in patients in Bumiayu Health Center with P value of 0.000 > 0.05.